Kolaborasi Perpustakaan Umum di Jakarta dalam Pengembangan Koleksi (Studi Kasus Sistem Jaklitera) - Anggraeni, Novita Cristyne; Dewi, Sarwendah Puspita (Pustabiblia: Journal of Library and Information Science, 2024)
This study explores the collaboration among public libraries in Jakarta regarding collection development through the Jaklitera system. The collaboration aims to enhance service accessibility by facilitating users through an interlibrary loan system among public libraries in Jakarta and integrating their catalogs. The research employs a descriptive qualitative method with a case study approach. Data were collected through interviews with two librarians involved in the development and management of the Jaklitera system. The findings indicate that Jaklitera significantly improves access to collections across various public libraries in Jakarta, regardless of the users' location. Additionally, the system helps libraries gather information on user collection needs, enabling them to respond more effectively. Despite its significant benefits, the study highlights challenges related to the technical adjustments required for integrating different library systems, as well as user adaptation to new technologies. This study recommends improving catalog standardization and developing digital collection services to enhance service quality and expand access to public library collections in Jakarta.